2010
DOI: 10.21061/jots.v36i1.a.7
|View full text |Cite
|
Sign up to set email alerts
|

<p>Advancing the “E” in K-12 STEM Education</p>

Abstract: Technological fields, like engineering, are in desperate need of more qualified workers, yet not enough students are pursuing studies in science, technology, engineering, or mathematics (STEM) that would prepare them for technical careers. Unfortunately, many students have no interest in STEM careers, particularly engineering, because they are not exposed to topics in these fields during their K-12 studies. Most K-12 teachers have not been trained to integrate relevant STEM topics into their classroom teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…The positive significance between the variable proves that students are aware that the robotic activities in the programmes does have links to knowledge of Mathematics. This result concurs with the study of Ronald et al (2010) which indicated that robotics is part of the STEM field.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The positive significance between the variable proves that students are aware that the robotic activities in the programmes does have links to knowledge of Mathematics. This result concurs with the study of Ronald et al (2010) which indicated that robotics is part of the STEM field.…”
Section: Resultssupporting
confidence: 92%
“…The field of robotics was chosen as robotics is considered as the core integration of mechanical, engineering, computer science and technology field. It is regarded as part of the STEM field (Ronald et al, 2010). The use of robots in education is considered demanding as the skills acquired by students venturing into the field are relevant to the current demand of work field (World Economic Forum, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through several screenings, we reviewed the abstracts of the articles and we excluded the following types of articles from this literature review study: (1) duplicate studies by exactly the same authors; (2) articles that aimed at investigating the effects of robotics kits and robotics environments with the objective of rehabilitation or with a clinical approach; (3) articles that targeted teachers as the main participants; (4) studies which used only software programs with virtual robots (not physical robots); and (5) research that included young children only for the purpose of user tests to develop robotics technology. Overall, 47 relevant articles were finally selected for our analysis ( Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…Robotics education provides learners with practical experiences for understanding technological and mechanical language and systems; accepting and adapting to constant changes driven by complex environments; and utilizing knowledge in real situations or across time, space, and contexts [1]. In addition, along with the growing attention to STEM (Science, Technology, Engineering, Mathematics) education, robotics has been suggested as an innovative solution [2,3]. Regardless of the economic and societal needs for new types of innovative and knowledgeable citizens, robotics has the attention of scholars as a means of "empowering learners" and providing "authentic learning".…”
Section: Introductionmentioning
confidence: 99%
“…The literature has pointed out that to change students' interest in STEM or their future career tendencies, STEM-related activities and curricula need to be added in high school (Rockland, Bloom, Carpinelli, Burr-Alexander, Hirsch, & Kimmel, 2010).To strengthen national competitiveness, there is a need to develop a large number of STEM talents (Langdon, McKittrick, Beede, Khan, & Doms, 2011). Therefore, it is very important to enhance high school students' awareness of STEM's application in the social environment and the cultivation of future professional interest.…”
Section: Research Claim 2: the Effect Of The Integrated Stem Curriculmentioning
confidence: 99%